2021
DOI: 10.1051/e3sconf/202125807091
|View full text |Cite
|
Sign up to set email alerts
|

The human impact in the age of digital transformation

Abstract: Issues of negative impact of digital processes on society in general and on people in particular are considered as well as problems of influence of network communications, virtual space, digitalization of education, formation of digital culture on personality. It is argued that in emerging digital society devalued the phenomenon of knowledge in the traditional sense, value and significant in practical terms, is not the possession of knowledge per se, but the ability to buy it, isolate of tremendous information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The possibility of forming a person's humanitarian culture throughout their life, its dynamic nature explain the emergence of the concept of "students' humanitarian culture" as an integral quality based on spiritual and intellectual qualities, and which characterizes the development of the student's personality, the level of their humanitarianism. In the digital era the content of the notion changes somewhat due to the conscious use of digital technologies, content and is explained by the context of digitalization in general (Kitova, 2018;Suroedova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of forming a person's humanitarian culture throughout their life, its dynamic nature explain the emergence of the concept of "students' humanitarian culture" as an integral quality based on spiritual and intellectual qualities, and which characterizes the development of the student's personality, the level of their humanitarianism. In the digital era the content of the notion changes somewhat due to the conscious use of digital technologies, content and is explained by the context of digitalization in general (Kitova, 2018;Suroedova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Modern researchers pay attention to the fact that the problem of attitude to one's appearance is of particular relevance in a digital society. The authors note that the solution to this problem is not so much the analysis and description of the new phenomenology of the psychology of appearance, but the determination of how the "digital being" of people, the emerging "new subjectivity", affect such fundamental phenomena as assessments, selfesteem, satisfaction and concern with appearance, perfectionism aimed at appearance [12,13,14,15]. In our previous studies devoted to the attitude of educators to their appearance, we found that despite the fact that in the conditions of the need to use distance learning, they are diagnosed with an average degree of satisfaction with their appearance, they note that they have an extremely negative attitude towards video filming [9].…”
Section: Features Of Non-verbal Communication In the Process Of Dista...mentioning
confidence: 99%
“…Both national and foreign studies emphasize the important role of all elements of nonverbal communication in the process of psychological counseling. Researchers draw attention to the fact that the appearance and non-verbal patterns of the client are an important source of information [11,15]. For example: appearance design (clothing, hairstyle) may indicate stratification and gender characteristics; expression (facial expressions, gestures, postures, etc.)…”
Section: Non-verbal Communication In Psychological Counseling and Its...mentioning
confidence: 99%
“…There are instances where digital technology substitutes for established technologies and tasks, yet in other scenarios, it functions in harmony with existing practices. Moreover, on occasion, the integration of digital technology leads to the emergence of novel activities, services, innovations, and business prospects (Suroedova et al, 2021;Sutton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%